PEMETAAN DEMOGRAFI DESA CIBURUY KECAMATAN PADALARANG KABUPATEN BANDUNG BARAT MELALUI KEGIATAN KULIAH KERJA NYATA - Euis Eti Rohaeti; Galih Dani Septiyan Rahayu (Jurnal Ilmiah P2M STKIP Siliwangi, 2019)
Community development in a village certainly should start from the existing potentials in the village both the potential of human resources and natural resources potential. To view these potentials need for demographic mapping of a village. Therefore, in this study the demographic mapping of Ciburuy village was carried out through real work activities. The purpose of this study was to map the demographics of Ciburuy village and to see the relevance of the real work activities of STKIP Siliwangi programs in Ciburuy village. The method used in this study is the qualitative research method. Data collection is done directly using the observation sheet and questionnaire. Demographic status  Ciburuy village  viewed from various fields, namely the field of population, education, health, religion, social and culture is the right village to be used as a village area guided by STKIP Siliwangi. Potentials that exist in Ciburuy consists of potential natural resources such as situ ciburuy, plantations, agriculture, fisheries, and limestone mines. Potential local products such as comring business, bamboo carving, making aquariums, making tables and chairs from Olympic materials, and making sequins. There is relevance between the real work program of STKIP Siliwangi and programs at Ciburuy village.